Perbandingan Kinerja Protokol AOMDV dan MP-DSR pada Mobile Ad Hoc Network (MANET) - Anugerah Wijaya; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Mobile Ad Hoc Network (MANET) is the development of wireless ad-hoc technology or now called Mobile Ad Hoc Network (MANET). The wireless interface becomes communication from one node to another and is also formed by several nodes. If a routing path can be optimal, then the routing protocol can include data exchange. Routing protocols analyzed include AOMDV and MP-DSR. The route discovery process is carried out when the source node will forward the destination node from the neighboring node that has received the packet. In MP-DSR, several destination nodes do mutual discovery, nodes will replace other alternatives if they experience troubIe during transmission. Packet delivery ratio, end to end delay, throughput packet loss, and convergence time are analysis of routing protocol performance parameters and tested through network simuIator 2. The conclusion from the analysis is that AOMDV routing protocol is better than the results of throughput, end to end deIay and normalized parameters. routing load, the averages obtained from the throughput of 26.200 kbps, the average value of the end to end delay is 159.3425 m/s and the normalized routing load is 0.7272. The MP-DSR routing protocol is better than the results of the packet delivery ratio and convergence time parameters, the averages of the packet delivery ratio are 0.998775% and the convergence time is 169.7896 m/s. The AOMDV routing protocol is better than the MP-DSR routing protocol seen from the Quality of Service (QOS) performance value of the increase in variation and node data packet size.